2002
DOI: 10.1097/00006199-200201000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, Resilience, and Depression in Midlife Women From the Former Soviet Union

Abstract: The results corroborate previous studies that suggest high levels of depression in immigrant women, but additional validation is suggested to differentiate symptoms of depressed mood from clinical depression in this culture. Findings also suggest that interventions that encourage use of English language and enhance resilience may help decrease symptoms of depression in midlife women who are recent immigrants from the former Soviet Union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 25 publications
8
105
1
3
Order By: Relevance
“…This may occur because of the gradual loss of protective cultural factors associated with greater acculturation and increased exposure to stressors that immigrants may not be equipped to handle (Escobar & Vega, 2000). On the other hand, it has been reported that acculturation is associated with lower rates of depression ; this was found among immigrants who reported greater English usage and more integrated social relationships (Escobar & Vega, 2000 ;Miller & Chandler, 2002). These authors have suggested that working and living near English speakers and exposure to English cultural events or media enhances psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…This may occur because of the gradual loss of protective cultural factors associated with greater acculturation and increased exposure to stressors that immigrants may not be equipped to handle (Escobar & Vega, 2000). On the other hand, it has been reported that acculturation is associated with lower rates of depression ; this was found among immigrants who reported greater English usage and more integrated social relationships (Escobar & Vega, 2000 ;Miller & Chandler, 2002). These authors have suggested that working and living near English speakers and exposure to English cultural events or media enhances psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly speaking, acculturation relates to the psychological, attitudinal and behavioral changes that occur due to the interaction between individuals from different cultures and the settlement society [24]. Acculturative stress associated with and the multiple changes/challenges (such as diet, climate, dress code, language and day-to-day routines) associated with it tend to impact immigrants' self esteem, identity, sense of belonging, meaning-making processes and by in large decrease women immigrants' mental health [25,26]. In particular, racialized WI face multiple oppressions such as racism, discrimination and unequal access to services [27][28][29].…”
Section: Acculturation and Mental Healthmentioning
confidence: 99%
“…Specifically, immigrant women have variously reported experiencing post-traumatic stress, multiple losses, adaptation stress, isolation, negative changes in identity, cognitive overload, discrimination, and violence (Berger, 2004;Espín, 1997Espín, , 1999Garza-Guerro, 1974;Yakushko & Chronister, 2005). Moreover, immigrant women who reported higher stress related to relocation showed considerably higher levels of depressive symptoms (Miller & Chandler, 2002).…”
Section: Iterature Review C Hallenges For Immigrant Womenmentioning
confidence: 99%